A Novel Dimeric Inhibitor Targeting Beta2GPI in Beta2GPI/Antibody Complexes Implicated in Antiphospholipid Syndrome - Kolyada, Alexey; Lee, Chang-Jin; De Biasio, Alfredo; Beglova, Natalia (PloS one, 2010)
β2GPI is a major antigen for autoantibodies associated with antiphospholipid syndrome (APS), an autoimmune disease characterized by thrombosis and recurrent pregnancy loss. Only the dimeric form of β2GPI generated by anti-β2GPI antibodies is pathologically important, in contrast to monomeric β2GPI which is abundant in plasma. We created a dimeric inhibitor, A1-A1, to selectively target β2GPI in β2GPI/antibody complexes. To make this inhibitor, we isolated the first ligand-binding module from ApoER2 (A1) and connected two A1 modules with a flexible linker. A1-A1 interferes with two pathologically important interactions in APS, the binding of β2GPI/antibody complexes with anionic phospholipids and ApoER2. We compared the efficiency of A1-A1 to monomeric A1 for inhibition of the binding of β2GPI/antibody complexes to anionic phospholipids. We tested the inhibition of β2GPI present in human serum, β2GPI purified from human plasma and the individual domain V of β2GPI. We demonstrated that when β2GPI/antibody complexes are formed, A1-A1 is much more effective than A1 in inhibition of the binding of β2GPI to cardiolipin, regardless of the source of β2GPI. Similarly, A1-A1 strongly inhibits the binding of dimerized domain V of β2GPI to cardiolipin compared to the monomeric A1 inhibitor. In the absence of anti-β2GPI antibodies, both A1-A1 and A1 only weakly inhibit the binding of pathologically inactive monomeric β2GPI to cardiolipin. Our results suggest that the approach of using a dimeric inhibitor to block β2GPI in the pathological multivalent β2GPI/antibody complexes holds significant promise. The novel inhibitor A1-A1 may be a starting point in the development of an effective therapeutic for antiphospholipid syndrome.